Principles and applications of One Health: Training of Somali academic and government professionals - Mumin, F.I.; Mor, Siobhan M.; Hared, Y.A.; Mohamed, S.A. (International Livestock Research Institute, 2025)
Somalia faces a complex and interconnected set of challenges at the human-animal-environment interface, including the risk of zoonotic disease outbreaks, antimicrobial resistance (AMR), environmental degradation, and persistent food insecurity. These challenges are especially acute in pastoralist and agropastoralist regions, where communities rely heavily on livestock and natural ecosystems for survival. However, despite the increasing urgency of these issues, Somalia still has limited structured One Health (OH) education and formal mechanisms for cross-sectoral collaboration. To address these gaps, a five-day training workshop titled “Principles and Applications of One Health” was conducted in Borama and Mogadishu, Somalia. The training was implemented under the Capacitating One Health in Eastern and Southern Africa (COHESA) project, with Amoud University the Somalia multiplier institution in partnership with Somali National University. The training content was based on Module 1 of the HEAL Project (One Health for Humans, Environment, Animals, and Livelihoods). The facilitation team included Professor Siobhan Mor (Chair of One Health, University of Liverpool; jointly appointed Principal Scientist, ILRI) and Farah Isse Mumin (PhD Fellow, University of Liverpool; Graduate Fellow, ILRI).